The field of the horticulturist - Dickens, Albert (My University, 1893)
Introduction: Horticulture, one of the oldest of arts, is yet as progressive as many more modern ones. Its development has been gradual, and as in all histories, the first pages of the history of horticulture are ranting. A twin sister of Agriculture, she combines with its practicability, an ardent love of the beautiful and has always worked to unite the useful and the ornamental.
Citation: Dickens, Albert. The field of the horticulturist. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Horticulture; Progressive; Histories; Agriculture; Theses; Manuscripts (documents)